Predicting Land-use and Land-cover Patterns Driven by Different Scenarios in the Emerald Triangle Protected Forests Complex - Trisurat, Yongyut; Bhumpakphan, Naris; Kalyawongsa, Suchat; Boonsermsuk, Sapol; Wisupakan, Kamol; Dechyosdee, Utai (วารสารวนศาสตร์ไทย, 2014)
The Emerald Triangle is the largest extensive intact block in the Greater Mekong Sub-region, which still remains along the tri-national borders between Thailand, Lao PDR and Cambodia. The remaining habitats are very important for the persistence of wide-ranging species in this area. This research aimed to assess land-use change in recent years and to predict land-use patterns across the Emerald Triangle landscape. The current land-use map was visually interpreted from satellite images and the rate of reduction was calculated accordingly. Future land-use patterns were predicted using the Dyna-CLUE model based on different land-use scenarios in 2030 defined by multi-stakeholders from the three countries. The model results indicated that dry dipterocarp forest in the north of Dong Khanthung provincial protected forest in Lao PDR and to the west of Pha Taem National Park in Thailand would be threatened by encroachment for agriculture and rubber plantation. If on restriction policy, parts of the Preah Vihear protected forest in Cambodia and Phou Xiang Thong National Biodiversity Conservation Area in Lao PDR would be converted for arable land in 2030. Evergreen forests were predicted as relatively intact as the current stage because they are found either inside protected areas or in steep terrains, thus become natural barriers for human-intervention. Keywords: CLUE-s model, Emerald Triangle, Land use scenarios, Trans-boundary biodiversity conservation